Students' Creativity and Engagement in Ecoprint-Based Art Learning Through the Project-Based Learning Model - Bagus Cahyanto; Evi Rizqi Salamah; Sela Kholidiani; Andini Retno Wulandari; Mega Nur Azizah Basuki (JENIUS (Journal of Education Policy and Elementary Education Issues), 2025)
This paper explores in depth the creativity and engagement of students in art learning with ecoprint techniques through a project-based learning model in elementary school. This research was conducted in a rural elementary school in Malang using a qualitative approach, with data collected through interviews, observations, and documentation. Data were analyzed using the interactive analytical model proposed by Miles, Huberman, and Saldana, which encompasses three stages: data condensation, data display, and conclusion drawing/verification. Data trustworthiness was ensured through source and technique triangulation. The findings indicate that the application of the Project-Based Learning model in arts instruction, using the ecoprint technique, significantly enhances students’ creativity and engagement in learning. The instructional process followed a systematic sequence that began with essential questions, designing a project plan, creating an activity schedule, supervising the project work, assessing the resulting product, and conducting an evaluation. This pedagogical practice successfully provided learners with a more contextual and experiential learning environment. Further research is recommended to implement this model in schools or grade levels with different typological characteristics, enabling more rigorous testing of its effectiveness across various educational contexts.